TQM and Competitive Advantage: A Review and Research Agenda - Chong, Sze Thiam; Ooi, Keng Boon; Chong, Alain Yee Loong; Tan, Boon In (Society for Alliance, Fidelity & Advancement, 2009)
The purpose of this paper is to develop a conceptual model that can be used in supporting the association between the many facets of total quality management (TQM) practices and its impact on competitive advantage. The theories of TQM and competitive advantage serve as the theoretical foundation to build up the conceptual model. This proposed conceptual framework could provide valuable knowledge to top management in the organizations to improve their quality management practices and subsequently achieving competitive advantage.